Fast algorithm and implementation of discrete cosine transform - Tan, Teng Chork. (2008)
The thesis aims to develop algorithms for fast computation of DCT for various sequence lengths. The algorithms developed should be as general as possible to allow the user to select a wide range of transform lengths. The algorithms should allow lower order DCT to be extended easily to higher order.